Are Patients with Coronavirus Disease 2019 and Obesity at a Higher Risk of Hospital and Intensive Care Unit Admissions? A Systematic Review and Meta-analysis - Wicaksana, Anggi Lukman; Hertanti, Nuzul Sri; Pramono, Raden Bowo; Hsu, Yu-Yun (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Obesity, common condition among patients with COVID-19, contributes to illness severity during hospitalization. To date, knowledge on the prevalence, risk of hospital and intensive care units (ICU) admissions and mortality is limited. Therefore, systematic review and meta-analysis were conducted using a PRISMA guideline. PURPOSE: The study aimed to address the prevalence, risk of hospital and ICU admissions and mortality among patients with COVID-19 and obesity. METHODS: The Newcastle–Ottawa scale was used to assess the quality of a study. Primary outcomes were the prevalence and risk of hospitalization, and secondary outcomes were the risk of ICU admissions and mortality risk. Mantel–Haenszel with random effects was applied, and the effect measure was odds ratio (OR) with 95% confidence interval (CI). RESULTS: Nine studies were included in the systematic review, and only four studies for meta-analysis. Among 29,776 patients with COVID-19, obesity was identified as the second-highest comorbidity. The prevalence rates of obesity and severe obesity among patients with COVID-19 were 26.1% and 15.5%, respectively. Obesity resulted in significantly increased risk of hospital admission (OR = 1.99, 95% CI = 1.12–3.53, p = 0.02) and ICU admission (OR = 1.77, 95% = CI 1.52–2.06, p < 0.00001). Severe obesity had a significantly increased risk of ICU admission (OR = 1.79, 95% CI = 1.42–2.25, p < 0.00001). The mortality rate of patients with COVID-19 and obesity was about 30.5% (438/1,434), and 19.7% (2,777/14,095) of them recovered from COVID-19. CONCLUSION: Obesity poses as nearly twice the risk of hospital and ICU admissions, and severe obesity contributes to almost twice the risk of ICU admissions.